2021
DOI: 10.1038/s41525-021-00243-3
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of rare variant associations to neurodegenerative disease presentation

Abstract: Genetic factors contribute to neurodegenerative diseases, with high heritability estimates across diagnoses; however, a large portion of the genetic influence remains poorly understood. Many previous studies have attempted to fill the gaps by performing linkage analyses and association studies in individual disease cohorts, but have failed to consider the clinical and pathological overlap observed across neurodegenerative diseases and the potential for genetic overlap between the phenotypes. Here, we leveraged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 52 publications
1
19
0
Order By: Relevance
“…Thirdly, neurodegenerative diseases might result from multiple rare variants, each unique in the affected person, and therefore be too rare for selection to have a significant impact. 46 With the increased availability of high-depth next generation sequencing, many rare variants have now been found to be associated with ALS 22 47 48 , Parkinson’s disease 23 49 and Alzheimer’s disease 50 51 , but common variants also contribute to risk. To address these hypotheses of how natural selection may have led to the persistence of common genetic risk variants of neurodegenerative disorders, we used stratified-LDSC to test the relationship between neurodegeneration-related SNPs and SNP-based signatures of natural selection.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, neurodegenerative diseases might result from multiple rare variants, each unique in the affected person, and therefore be too rare for selection to have a significant impact. 46 With the increased availability of high-depth next generation sequencing, many rare variants have now been found to be associated with ALS 22 47 48 , Parkinson’s disease 23 49 and Alzheimer’s disease 50 51 , but common variants also contribute to risk. To address these hypotheses of how natural selection may have led to the persistence of common genetic risk variants of neurodegenerative disorders, we used stratified-LDSC to test the relationship between neurodegeneration-related SNPs and SNP-based signatures of natural selection.…”
Section: Discussionmentioning
confidence: 99%
“…The other MAPT variant (p.Ala41Thr) occurred in a patient also carrying a pathogenic mutation in the FUS gene (AD#039). Due to the heterogeneity of genetic factors contributing to neurodegeneration, pathogenic/likely pathogenic variants and VUS have been considered as weak allele risk factors ( Dilliott et al, 2021 ). Carriers of these variants were equally distributed between the familial and sporadic groups (Fisher exact test p -value = 1).…”
Section: Resultsmentioning
confidence: 99%
“…In agreement with this hypothesis, Spina et al, 2021, found at least one non-AD neuropathological diagnosis in 98% of patients with EOAD. Due to the heterogeneity of genetic factors contributing to neurodegeneration, and the equal distribution between sporadic and familial forms, we consider pathogenic/hypothetical pathogenic variants and variants with 10.3389/fnagi.2022.969817 uncertain significance in these genes to be weak risk factors (Dilliott et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found a high frequency of the p.Arg402Cys variant in the PARK2 gene in the ALS cohort. This variant is classified as a variant of uncertain significance in ClinVar and has been also recently found to be increased in a FTD cohort [ 36 ], where the authors speculated the possible role of the PARK2 gene in the pathogenesis of FTD, highlighting the possible overlap across neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%